2010
DOI: 10.1088/0957-4484/21/36/365701
|View full text |Cite
|
Sign up to set email alerts
|

Charge-selective transport of organic and protein analytes through synthetic nanochannels

Abstract: We present an experimental demonstration of a synthetic nanoporous membrane suitable for charge-selective transport of ionic species. The surfaces and walls of synthetic nanochannels, fabricated in heavy ion-tracked polyethylene terephthalate membranes are negatively charged due to the presence of carboxylate moieties. These nanofilters discriminate and gate the transport of cations while inhibiting the passage of anions. The permselectivity of these membranes is reversed by converting the carboxylic moieties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
(72 reference statements)
1
39
0
Order By: Relevance
“…Cylindrical nanopores were fabricated through a previously published method. [14] Briefly, the PET films were pre-treated with UV light (approximately 4.2 mW cm À2 ) for 1 h on each side before etching with NaOH (2 m) at 50 8C for 8 min (Supporting Information). After that, the films were thoroughly washed with and restored in distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cylindrical nanopores were fabricated through a previously published method. [14] Briefly, the PET films were pre-treated with UV light (approximately 4.2 mW cm À2 ) for 1 h on each side before etching with NaOH (2 m) at 50 8C for 8 min (Supporting Information). After that, the films were thoroughly washed with and restored in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…[14] The mean diameter of the nanopores for the sensor was 79 AE 7 nm and the pore density was approximately 5 10 8 cm À2 (Supporting Information, Figure S2). [14] The mean diameter of the nanopores for the sensor was 79 AE 7 nm and the pore density was approximately 5 10 8 cm À2 (Supporting Information, Figure S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Cylindrical Nanochannel Array : For this purpose, PET membranes irradiated with 5 × 10 8 ions cm −2 were used. The fabrication of cylindrical nanochannels was achieved by the symmetric track‐etching technique 60. Polymer membranes fixed in a sample holder were immersed in the pre‐heated etching solution.…”
Section: Methodsmentioning
confidence: 99%
“…Studying how molecules interact with the single nanopore at the nanoscale level is the foundation of constructing nanopore-based biosensing platform. Nowadays, a number of interaction patterns between the functional nanopore surface and the target analytes such as the hydrophobic interaction [8], electrostatic interaction [24], bio-specific interaction [10,20,25] and metal-chelating interaction [11,12] have been investigated inside the synthetic nanopore channels, thus suggesting the construction of promising platforms for sensing the protein molecules. Previously, Ali et al [8] has reported covalently modifying single asymmetric nanochannels in polyethylene terephthalate (PET) membranes with ethylenediamine or propylamine to manipulate the charge polarity and hydrophobicity of the nanochannel, respectively.…”
Section: Introductionmentioning
confidence: 99%